THE INFLUENCE OF FACTORS IN LOCAL GOVERNMENT FINANCIAL MANAGEMENT ASPECTS TO THE REMAINING BUDGET (SILPA) IN THE CITY OF TARAKAN - Ninuk Sri Wanarni (ABIS: Accounting and Business Information Systems Journal, 2013)
SiLPA occur almost in every local government in Indonesia. SiLPA may occur due to the realization of revenue targets or exceeding a set budget and actual expenditures that are less than the predetermined budget. The high and low SiLPA not necessarily indicate good performance of the local government concerned. Still needed a deeper study to assess whether SiLPA shown in the LRA is an achievement or otherwise. Several factors must be considered to assess whether SiLPA SiLPA shown in the Statement of Budget Realization is an achievement or otherwise. Several factors must be considered in assessing SiLPA , namely the reform of local government financial management, local government revenue management, local government expenditure management, local government cash management and cash budget, local government asset management, local government debt management and investment, and the management of local government partnerships. These factors are summarized in the overall Local Government Financial Management. This study seeks to uncover the influence of these factors in the area of local government financial management aspects of the SiLPA . The hypothesis is built is that these factors positively influence SiLPA . This research was conducted in the City of Tarakan to sample some employees in SKPD and a financial manager SiLPA largest producer. Analysis of the data in this study using multiple linear regression, with the program SPSS 20. The results of this study indicate that the local government revenue management, local government expenditure management, local government cash management and cash budget, local government asset management, local government debt management and investment, and the management of local government partnerships positive give effect on SiLPA. The reform of local government financial management does not give a positive effect on SiLPA.